Reusing negotiation strategy for multi-agent system development - Lu, Marlene Valerie Ai siok (Universiti Malaysia Sarawak, (UNIMAS), 2013)
The dynamic nature of the agent technology and the inherent characteristics of the agent are aptly suited in the implementation of a negotiation system. Even with such a promising technology, the development of the multi-agent negotiation system is not widely accepted by the software community. With a lack of standardised approach in the development process, it has become a deterrent for software developers to adopt the agent technology, as it is laborious to learn and to reinvent the wheel in the development of multi-agent negotiation systems. Thus, this research is carried out with the intention to alleviate the gap identified by proposing an alternative approach through the use of agent negotiation patterns. Agent patterns are used to document the multi-agent system development experience and to provide a generic solution to recurring problems within a problem domain. Through that, the agent's conceptual designs are reusable to expedite development process and to provide a structured guideline to the development of the multi-agent negotiation system. To provide a comprehensive description of the agent negotiation patterns, a pattern template by WaiShiang(2010) is used as a basis for documenting the patterns in an organised manner. The pattern template identifies the elements required to describe the multi-agent negotiation system at different levels of abstraction. In this research, the pattern template uses the AOR/ROADMAP models (Taveter & Sterling, 2008) to depict the agent's concepts. Based on the pattern template, nine patterns are derived for different negotiation strategies, which are adapted from the existing research works. To evaluate and demonstrate the reusability of the agent negotiation patterns derived, two patterns are used in the practical implementation of a case study. Coupled with that, quantitative evaluation is performed. Two evaluators are selected to analyse the viability of the agent negotiation patterns, and questionnaires are used to capture various metrics. The outcome from the two evaluation techniques prove that the patterns are reusable, extensible and adaptable